Utilization of Social Media as a Promotional Strategy to Increase Sales - Prayogo, Ahmat; Anshori, Mochammad; Andriani, Nurita (Jurnal Ilmiah Manajemen Kesatuan, 2023)
In this digital era, social media has become a very significant platform as a marketing strategy and business promotion tool. This research aims to explore and analyze strategies for using social media as an effective promotional tool to increase sales of a product. In this research, the method used is Systematic Literature Review (SLR) to identify, evaluate, and interpret research results that are relevant to a particular research question, or topic area, or phenomenon of concern (Kitchenham, 2004). The method for writing this literature review article uses the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. It can be concluded that in the digital era with the ever-increasing growth of social media users, social media is useful for small and medium businesses or large companies as an effective promotional media because social media has a wide reach, precise targeting, high involvement between brands and consumers. Easy sharing capabilities and has analysis and performance measurement for evaluation. The use of social media as sales support also has many platform options that can be chosen according to the needs of businesspeople, such as Marketplace Facebook, Instagram, Tiktok, and Youtube.